A Utilização do Software Unreal Engine na Pré-Visualização de Cenas de Cinema e Televisão - Diogo Manuel Pinto Ganilho Esteves (2021)
The interest and curiosity in real time visualization technologies applied to audiovisual projects has been growing exponentially. This study aims to analyze the application of Unreal Engine® (Epic Games, Inc, North Carolina, EUA), a real time game engine, in the first steps of an audiovisual project and to address its applicability as an artistic and technical tool to facilitate the production methods used by creatives. This study comprises: i) revision of historical context on methods and Previsualization technologies; ii) development of Previsualization exercise approaching both traditional and virtual methodologies, using Unreal Engine, aiming to analyse and compare both practices during the different stages of a Previsualization process; iii) assessment of the potential advantages and disadvantages of of Unreal Engine application in Previsualization. From the analysis of the retrieved information and experience gained through the process of the proposed project´s development, it is concluded that the way Preproduction and Visualization are being approached is in fact rapidly changing. Real time technology is driving a new paradigm in audiovisual productions and Unreal Engine has become one of the most important elements in its development and implementation.